Engineering resveratrol-loaded chitosan nanoparticles for potential use against Helicobacter pylori infection - Spósito, Larissa [UNESP]; Fonseca, Diana; Gonçalves Carvalho, Suzana [UNESP]; Sábio, Rafael Miguel [UNESP]; Marena, Gabriel Davi [UNESP]; Bauab, Taís Maria [UNESP]; Bagliotti Meneguin, Andréia [UNESP]; Parreira, Paula; L. Martins, M. Cristina; Chorilli, Marlus [UNESP] (Elsevier, 2024)
Helicobacter pylori (H. pylori) is a microorganism directly linked to severe clinical conditions affecting the stomach. The virulence factors and its ability to form biofilms increase resistance to conventional antibiotics, growing the need for new substances and strategies for the treatment of H. pylori infection. The trans-resveratrol (RESV), a bioactive polyphenol from natural sources, has a potential activity against this gastric pathogen. Here, Chitosan nanoparticles (NP) containing RESV (RESV-NP) were developed for H. pylori management. The RESV-NP were prepared using the ionic gelation method and characterized by Dynamic Light Scattering (DLS), Nanoparticle Tracking Analysis (NTA) and, Cryogenic Transmission Electron Microscopy (Cryo – TEM). The encapsulation efficiency (EE) and in vitro release rate of RESV were quantified using high-performance liquid chromatography (HPLC). RESV-NP performance against H. pylori was evaluated by the quantification of the minimum inhibitory/bactericidal concentrations (MIC/MBC), time to kill, alterations in H. pylori morphology in its planktonic form, effects against H. pylori biofilm and in an in vitro infection model. RESV-NP cytotoxicity was evaluated against AGS and MKN-74 cell lines and by hemolysis assay. Acute toxicity was tested using Galleria mellonella model assays. RESV-NP showed a spherical shape, size of 145.3 ± 24.7 nm, polydispersity index (PDI) of 0.28 ± 0.008, and zeta potential (ZP) of + 16.9 ± 1.81 mV in DLS, while particle concentration was 3.12 x 1011 NP/mL (NTA). RESV-NP EE was 72 %, with full release within the first 5 min. In microbiological assays, RESV-NP presented a MIC/MBC of 3.9 µg/mL, a time to kill of 24 h for complete eradication of H. pylori. At a concentration of 2xMIC (7.8 µg/mL), RESV-NP completely eradicated the H. pylori biofilm, and in an in vitro infection model, RESV-NP (4xMIC – 15.6 µg/mL) showed a significant decrease in bacterial load (1 Log10CFU/mL) when compared to the H. pylori J99 control. In addition, they did not demonstrate a toxic character at MIC concentration for both cell lines. The use of the RESV-NP with mucoadhesion profile is an interesting strategy for oral administration of substances targeting gastric disorders, linked to H. pylori infections.
Keywords: Antibacterial activity; Drug delivery system; Gastric infection; Helicobacter pylori; Polymeric nanoparticles; Trans-resveratrol